THE NECESSITY OF APPLYING DIGITAL TECHNOLOGIES IN DETERMINING TAX BENEFITS - Dehqonov G‘ayratjon Raximovich (Journals Park Publishing, 2025)
In Uzbekistan, the introduction of digitalization systems is of great importance in improving the efficiency of tax incentives and their accurate assessment. This article analyzes the role of digital technologies in assessing the efficiency of tax incentives, their advantages and potential problems. Digital solutions create the opportunity to automate tax information, conduct real-time monitoring and make informed decisions based on an analytical approach. Digitalization also strengthens mutual trust between taxpayers and the state and increases economic efficiency.
Keywords: Tax incentives, digitalization, efficiency, tax system, economic analysis.